Mechanistic insights into plasmonic photocatalysts in utilizing visible light - Leong, Kah Hon; Aziz, Azrina Abd; Sim, Lan Ching; Saravanan, Pichiah; Jang, Min; Bahnemann, Detlef (Beilstein Journal of Nanotechnology, 2018)
The utilisation of sunlight as an abundant and renewable resource has motivated the development of sustainable photocatalysts that can collectively harvest visible light. However, the bottleneck in utilising the low energy photons has led to the discovery of plasmonic photocatalysts. The presence of noble metal on the plasmonic photocatalyst enables the harvesting of visible light through the unique characteristic features of the noble metal nanomaterials. Moreover, the formation of interfaces between noble metal particles and semiconductor materials further results in the formation of a Schottky junction. Thereby, the plasmonic characteristics have opened up a new direction in promoting an alternative path that can be of value to the society through sustainable development derived through energy available for all for diverse applications. We have comprehensively prepared this review to specifically focus on fundamental insights into plasmonic photocatalysts, various synthesis routes, together with their strengths and weaknesses, and the interaction of the plasmonic photocatalyst with pollutants as well as the role of active radical generation and identification. The review ends with a pinnacle insight into future perspectives regarding realistic applications of plasmonic photocatalysts.
Keywords: localized surface plasmon resonance (LSPR); noble metal; plasmonic photocatalyst; reactive radicals; Schottky junctions; visible light